Salvianolic acids for injection alleviates cerebral ischemia-induced neurodegeneration by inhibiting endoplasmic reticulum stress and neuroinflammation - Wen Zhang; Sen Zhang; Haiguang Yang; Yangyang He; Xue Zhang; Rong Yan; Junke Song; Xiaobin Pang; Guanhua Du (Elsevier, 2023)
Background: Cerebral ischemia is one of the leading causes of neurological deficit, dementia, and disability globally. Salvianolic acids for injection (SAFI), a multi-component drug derived from Salvia miltiorrhiza L., has been clinically used in China to treat ischemic stroke. Purpose: This study was designed to investigate the mechanisms of SAFI in alleviating cerebral ischemia-induced neurodegeneration, especially its regulatory effects on excessive ER stress. Basic procedures: The rat acute cerebral ischemic injury model was established by a 1.5 h occlusion of the middle cerebral artery followed by 24 h of reperfusion. The neurological deficits, neurobehavior, cerebral infarct volume and edema of rats were examined. Hematoxylin and eosin staining, transmission electron microscopy analysis and TUNEL staining were performed to study the brain injury and cell apoptosis. Western blot and immunofluorescence assay were carried out to study the effects and mechanism of SAFI on ischemic injury. Main findings: Results showed that SAFI significantly inhibited the acute neurodegeneration, reduced brain infarct volumes and decreased brain water content of rats. SAFI also downregulated the relative protein levels of Bax/Bcl-2, Bim, Caspase-12, and reduced the number of TUNEL-positive cells in brain tissue, indicating the anti-apoptotic effects of SAFI. Both of immunofluorescence assay and western blot results showed that SAFI downregulated the expression of endoplasmic reticulum (ER) stress maker GRP78. SAFI dramatically inhibited the ER stress-related PERK/eIF2α/ATF4/CHOP and IRE1α/TRAF2/ASK1/JNK signaling pathways. SAFI also alleviated NF-κB triggered inflammatory response, and inhibited the production of IL-6 and IL-β. Conclusions: Our studies indicated that inhibition of excessive ER stress contributes to the protective effects of SAFI against cerebral ischemia-induced neurodegeneration and neuroinflammation.